2012
DOI: 10.1590/s0104-42302012000500016
|View full text |Cite
|
Sign up to set email alerts
|

Adequação calórico-proteica da terapia nutricional enteral em pacientes cirúrgicos

Abstract: Inadequate caloric and protein intake was common, which can be attributed to complications and diet suspensions during ENT, which may have hampered the sample reached their nutritional needs. This may contribute to the decline in the nutritional status of surgical patients, who often have impaired nutrition, as observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
0
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
2
0
0
4
Order By: Relevance
“…Nevertheless, low calorie and protein intakes were observed regardless of the route of feeding. These results were corroborated by other studies 24 which found that enteral feeding does not ensure adequate calorie intake, especially in patients undergoing intensive therapy 25 . Parenteral nutrition may be better able to meet caloric requirements 26 , but this could not be verified by the present study as few patients (0.8%) received such feeding.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, low calorie and protein intakes were observed regardless of the route of feeding. These results were corroborated by other studies 24 which found that enteral feeding does not ensure adequate calorie intake, especially in patients undergoing intensive therapy 25 . Parenteral nutrition may be better able to meet caloric requirements 26 , but this could not be verified by the present study as few patients (0.8%) received such feeding.…”
Section: Discussionsupporting
confidence: 81%
“…A similar result was found in the study by Isidro and Lima (2012), with fasting for procedures being the biggest reason for suspension of the enteral diet (84.6%), followed by nausea/emesis (38.5%). In addition to diarrhea and vomiting, gastroparesis is another gastrointestinal complication associated with the use of ENT.…”
Section: Discussionsupporting
confidence: 88%
“…Observou-se, neste estudo, uma alta prevalência de inadequação calórica e proteica, resultados semelhantes aos encontrados na literatura [23][24][25][26][27][28] . A luta contra o deficit de calorias e proteínas em pacientes de UTI com TNE exclusiva é diária.…”
Section: I S C U S S ã Ounclassified